MEMPERERAT KERUKUNAN UMAT BERAGAMA DI DESA MEDAN SENEMBAH - Ali Akbar; Fatur Rahman; Mega Aini Ananda Sihombing; Riska Saragih; Sri Kartika Dewi (STIT AL-AMIN KREO TANGERANG, 2021)
This study aims to analyze efforts to strengthen religious harmony in Medan Senembah Village, North Sumatra. This study uses descriptive qualitative research methods that aim to make the reality easier to study. The results of this study indicate that inter-religious harmony in Medan Senembah Village is very well demonstrated by the never occurring friction between religious communities due to the high tolerance and participation of each religious community in religious events in the local area. Medan Senembah village also makes interactive dialogues between religious leaders and the community to be open to each other with religious issues so that they can mobilize energy together to build a harmonious and peaceful society.